The contest for the tall forests of south-western Australia and the discourses of advocates - Wardell-Johnson, Grant; Wardell-Johnson, Angela; Schultz, B.; Dortch, J.; Robinson, Todd; Collard, L.; Calver, M. (Surrey Beatty and Sons, 2018)
After over 50 000 years of interaction between Aboriginal people and changing climates, south-western Australia's tall forests were first logged less than 200 years ago, initiating persistent conflict. Recent conservation advocacy has resulted in the protection of 49% of these tall forests in statutory reserves, providing an opportunity to implement and benefit from a growing moral consensus on the valuing of these globally significant, tall forest ecosystems. We analysed a cross-section of literature (63 papers, 118 statements) published on these forests over 187 years to identify values framing advocacy. We differentiated four resource-oriented discourses and three discourses giving primacy to social and environmental values over seven eras. Invasion sparked initial uncontrolled exploitation, with the Forests Act 1918 managing competing agricultural and timber advocacy. Following the Colonial and Country Life eras, industrial-scale exploitation of the karri forest region resulted in reaction by increasingly broad sectors of society. Warming and drying in the 21st Century emphasises the importance of intact tall forest and the Indigenous Renaissance discourse. Vesting for a more comprehensive set of values would acknowledge a new moral consensus.